Respuesta :

Answer:

 (2h-3k)^2           [(2h-3k)^2] x 6hk             6hk(2h-3k)

------------------ =  ---------------------------   = ------------------------

  5(2h-3k)               5(2h-3k)                             5  

  --------            

   6hk

   

Step-by-step explanation:

after 1st equation, move 6hk to top, this is because (b is 1 in this case):

    a

  -----

    b

------------- = (a/b) / (c/d) = (a/b) * (d/c) = (a*d)/(b*c)

    c

   ----

     d

after 2nd equation, crossed out (2h-3k)

ACCESS MORE